Miniaturized Infusion Monitoring System with Weight Sensor (Load Cell) Based on AT-MEGA 328 Microcontroller - Daswara Djajasasmita; M. Reza Hidayat; Susanto Sambasri (International Journal of Industrial Research and Applied Engineering, 2021)
The development of medical equipment with advanced technology can provide convenience in providing services to the community. One of the equipment that is in the hospital and most often used is an IV. In its use, manual infusion is used to determine the volume of the infusion and must be monitored every hour or even minute by the nurse. This is considered quite difficult, especially in the era of the Covid-19 pandemic where minimal interaction is required from 2 individuals. This is done by utilizing sensor technology to monitor the patient's condition so that the frequency of the nurses checking the condition of the infusion is getting less. Therefore, in this research, manufactured of an infusion monitoring system using aweight sensor (Load Cell) based on the ATMEGA 328 microcontroller was carried out. The sensor of this monitoring system uses a Load Cell Weight Sensor with the HX711 module which is integrated into the ARDUINO UNO MCU. The output of the system is displayed on a 16 x 2 mm LCD as well as a Macro Excel which will display the percentage value of intravenous fluids in the PC and real-time automatic data logging into the macro excel. The infusion used uses Nacl fluid infusion. The test results of the system as a whole show that the data for measuring levels (%) of intravenous fluids can be sent and displayed on the LCD and PC. The incoming data is converted into a table at certain time intervals according to the user's choice into the operator. The experiment was carried out 10 times by looking at changes in the contents of the infusion fluid over time in 11 stages where the LED lights up when the weight of the infusion reaches 40 - 46 grams. Then, the buzzer and LED have turned on when the weight of the infusion is less than 5 grams. From the experiment, it can be concluded the 10% setpoint alarm works well, i.e. when the infusion load is less than the 1% set point, the buzzer and LED will light up until the intravenous fluid is replaced with a new one.